2007
DOI: 10.1144/gsl.sp.2007.271.01.25
|View full text |Cite
|
Sign up to set email alerts
|

Differences in texture, physical properties and microbiology of weathering crust and host rock: a case study of the porous limestone of Budapest (Hungary)

Abstract: Ashlars of the Parliament building and Citadella fortress made of three porous Miocene limestones, a fine-grained limestone, a medium-grained oolitic limestone and a coarse-grained bioclastic limestone, were studied and compared with quarry blocks of the same lithologies. The commonest weathering forms are white (thin and thick) and black (laminar and framboidal) crusts. To assess the processes of crust formation and detachment, descriptions of lithologies and associated weathering features were combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The major difference between the decay mechanism of sandstone and porous limestone is in the dissolution and re-precipitation process. The crust on limestone can form an almost uniform seal with minor or no porosity (Török 2003;Török et al 2007), while in the sandstone case hardening is also a sign of porosity loss, although the pores in sandstone are rarely occluded entirely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major difference between the decay mechanism of sandstone and porous limestone is in the dissolution and re-precipitation process. The crust on limestone can form an almost uniform seal with minor or no porosity (Török 2003;Török et al 2007), while in the sandstone case hardening is also a sign of porosity loss, although the pores in sandstone are rarely occluded entirely.…”
Section: Discussionmentioning
confidence: 99%
“…Kieslinger 1949;Amoroso and Fassina 1983). The most common form of weathering on limestone is the development of gypsum crusts, as has been known from many cities (Amoroso and Fassina 1983;Antill and Viles 1999;Lefèvre and Ausset 2002;Fassina et al 2002;Smith et al 2002Smith et al , 2003Török 2002;Thornbush and Viles 2004;Török and Rozgonyi 2004;Smith and Viles 2006;Török et al 2007). Crust formation is mostly attributed to the transformation of calcium carbonate into calcium sulfate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on field studies of existing monuments that are found in urban areas including marbles (Moropoulou et al 1998;Maravelaki-Kalaitzaki and Biscontin 1999) and various types of limestone (Amoroso and Fassina 1983;Viles 1993;Fobe et al 1995;Török 2002;Gaviňo et al 2004;Smith and Viles 2006;Siegesmund et al 2007;Török et al 2007). So far, only a few papers have dealt with monuments found in rural areas far from urban pollution fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Török focused on different types of crusts (e.g., black encrustations, white crusts, etc.) of soft oolitic limestone [5,6] as well as travertine [7] and tuffs [8]. Akin and Ozsan also classified travertine [9], specifically Eskipazar yellow traverine, which is widely used in Turkey.…”
Section: Introductionmentioning
confidence: 99%